Vertrag zu Rechten Dritter Ausgewählte Schriften 1970-2010 - Hadding, Walther (Mohr Siebeck, 2024)
This collection of essays deals with the legal rules of Germanys »Vertrag zu Rechten Dritter«, which gave rise to the introduction in England and Wales of the Contracts (Rights of Third Parties) Act in 1999 and ended the need to use trust law.
PublicationDate: 20241018
Keywords: Zivilrecht -- Allgemeines Schuldrecht -- Auslegungsfragen zu den §§ 328-335 BGB -- Zweckänderung -- Pressearbeit -- Transaktionen mit nahestehenden Personen -- Treuhänderisches Unternehmertum -- Bürgerliches Recht